Kepemimpinan Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Agama Islam - haeruddin, haeruddin; Parhan, Parhan (Jurnal Manajemen & Budaya, 2024)
The purpose of this research to find out the Leadership of School Principals in Increasing the Professionalism of Islamic Teachers. Data collection techniques use observation, interviews and documentation. Research resultshows that 1. The leadership of school principals in increasing the professionalism of Islamic religious teachers prioritizes family aspects with a leadership typology that is legal and rational. 2. Factors that support increasing the professionalism of Islamic religious teachers come from Islamic religious teachers themselves, where even though they have standard abilities, there is still a desire to improve and become even better accompanied by real effort. The factors that inhibit it are divided into two, namely, first: the inhibiting factor for madrasas whose main milestone is caused by weak financial factors which have an impact on others such as the lack of facilities and infrastructure as well as media in learning and the low level of education. 3. Efforts made by madrasa heads to increase the professionalism of Islamic religious teachers, namely by coaching and supervising Islamic religious teachers, improving the welfare of Islamic religious teachers, sending Islamic religious teachers to take part in scientific activities, activating teachers in MGMP and motivating religious teachers Islam to study